The Kinetics and Mechanism of Lead (II) Adsorption in Different Types of Contactor by Powderized Rhizopus Oligosporus - Mel, Maizirwan (1998)
The effect of sorption conditions on the rate and capacity of lead uptake by powderized biomass of Rhizopus oligosporus was first carried out in shake flask experiments. Lead sorption by Rhizopus oligosporus was also investigated in different types of contactor such as stirred tank bioreactor, airlift fennenter and packed-bed column. The experimental data of lead adsorption in different sorption conditions (pH, temperature, solution viscosity, lead and biomass concentration) and different operating variables of the contactor (agitation speed and air flow rate) were analysed using Langmuir and Freundlich sorption isotherm models. The mechanism of lead uptake by the cell was examined using TEM micrograph, EDXA and FTIR photoacoustic. The experimental data of lead sorption by Rhizopus oligosporus fitted well to Langmuir and Freundlich sorption isotherm models, indicating that the sorption was similar to that for ion-exchange resin. This means that the sorption is a single layer metal adsorption which occured as a molecular surface coverage. This assumption was confirmed by the examination of lead sorption using TEM micrograph, EDXA and FTIR photoacoustic, which showed that during sorption most of lead was adsorbed on the surface of cell.From shake flask experiment, it was found that the biomass concentration and initial solution pH optima for lead sorption at initial lead concentration ranging from 50-200 mglL was 0.5 g/L and pH 5, respectively. In term of the ratio of initial lead concentration to biomass concentration, the optimum value for lead sorption was 750 mg/g. In all types of contactor investigated, maximum lead uptake capacity increased with increasing temperature and drastically decreased with increasing solution viscosity. Lead adsorption kinetic parameters values, calculated using Langmuir and Freundlich models, were significantly varied with sorption condition. Intraparticle diffusion rate constant (Kp) and equilibrium adsorption rate (Kₐ decreased with increasing solution viscosity, while diffusion coefficient (D) increased with increasing solution viscosity. On the other hand, D was decreased with increasing temperature while Kad was not significantly different at different temperatures. When 5 L stirred tank bioreactor was used as a contactor, the highest lead uptake capacity was obtained at agitation speed ranging from 50-150 rpm (Re = 3,900 - 11,700). On the other hand, the optimum air tlowrate for lead sorption in 2 L airlift fermenter was obtained at 2 vvm. Increased in the degree of turbulence as created by increased in degree of agitation (stirred tank bioreactor) and air flowrate (airlift fermenter), significantly reduced Kad and D but has no effect on Kp- The maximum lead uptake capacity obtained in shake flask, stirred tank bioreactor and airlift fermenter at optimum sorption conditions was 126, 79 and 74 mglg, respectively. Absolute removal of lead ions from solution was achieved when fixed packed-bed column was used as a contactor. However, the maximum lead uptake capacity (24 mg/g) was 3 times lower than that obtained in stirred tank bioreactor or an airlift fermenter.